The importance and usefulness of corporate annual reports in Malaysia: views of preparers and users - Mohd Ghazali, Nazli Anum (IIUM Press, 2009)
This study examines the importance and usefulness of corporate annual reports in Malaysia. Unlike prior research, which investigates the users' perceptions (e.g. Anderson, 1981; Abu Nassar and Rutherford, 1996; Naser et al, 2003; Al-Razeen and Karbhari, 2004; Mirshekary and Saudagaran, 2005), this study looks at the perceptions of preparers and users of corporate annual reports in an attempt to find if there is a gap between what users and preparers perceived about annual reports. A questionnaire survey was carried out to elicit opinions from the chief financial officers and investment analysts. The findings appear to suggest that while preparers regarded the annual reports as the most importance source of corporate information, users ranked the annual report second importance after visits to company and communication with the managements. The difference in opinions regarding the importance of visits to company and communication with the management was found to be statistically significant at the 5% level. Nonetheless, both groups of respondents were of the same view that the income statement and cash flow statement were the most important sections of the annual reports. The Chairman's Statement was found to be least important. On the issue of current disclosures in annual reports are already adequate, preparers believed that they need slight improvement (mean score = 2.35) while users felt that some improvements are required (mean score + 3.06). Preparers and users had different opinions on whether there should be more disclosure, preparers tend to agree moderately (mean score = 3.53). These differences were statistically significant at 5% level. Although a higher proportion of users were of the opinion that additional disclosures should be mandated, the proportion was not significantly different from that of preparers.